KONSEP PEMIKIRAN PENDIDIKAN MENURUT SYAIKH AZ-ZARNUJI DALAM KITAB TA'LIMUL MUTA’ALIM - Muhammad Ibnu Faruq Fauzi (STAI Sangatta Kutai Timur, 2022)
Az-Zarnuji's thoughts in the book of Ta'limul Muta'allim contain adab-adab in education about student learning morals and teacher character. The focus of this research is How does Az-Zarnuji think about education in the book of Ta'limul Muta'allim? The research method is qualitative research in the form of library research (library research) In order to get valid research results, it is necessary to select sources, both primary data sources and secondary data sources. The primary data source of this research is the book